Autologous hematopoietic stem cell transplantation for multiple myeloma in the age of CAR T cell therapy - Hughes, Charlotte F. M.; Shah, Gunjan L.; Paul, Barry A. (Frontiers in Oncology, 2024)
Chimeric antigen receptor (CAR) T cell therapy has revolutionized the management of relapsed and refractory myeloma, with excellent outcomes and a tolerable safety profile. High dose chemotherapy with autologous hematopoietic stem cell transplantation (AHCT) is established as a mainstream of newly diagnosed multiple myeloma (NDMM) management in patients who are young and fit enough to tolerate such intensity. This standard was developed based on randomized trials comparing AHCT to chemotherapy in the era prior to novel agents. More recently, larger studies have primarily shown a progression free survival (PFS) benefit of upfront AHCT, rather than overall survival (OS) benefit. There is debate about the significance of this lack of OS, acknowledging the potential confounders of the chronic nature of the disease, study design and competing harms and benefits of exposure to AHCT. Indeed upfront AHCT may not be as uniquely beneficial as we once thought, and is not without risk. New quadruple-agent regimens are highly active and effective in achieving a deep response as quantified by measurable residual disease (MRD). The high dose chemotherapy administered with AHCT imposes a burden of short and long-term adverse effects, which may alter the disease course and patient's ability to tolerate future therapies. Some high-risk subgroups may have a more valuable benefit from AHCT, though still ultimately suffer poor outcomes. When compared to the outcomes of CAR T cell therapy, the question of whether AHCT can or indeed should be deferred has become an important topic in the field. Deferring AHCT may be a personalized decision in patients who achieve MRD negativity, which is now well established as a key prognostic factor for PFS and OS. Reserving or re-administering AHCT at relapse is feasible in many cases and holds the promise of resetting the T cell compartment and opening up options for immune reengagement. It is likely that personalized MRD-guided decision making will shape how we sequence in the future, though more studies are required to delineate when this is safe and appropriate.